2021
DOI: 10.1177/15248380211021613
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Biological Correlates and Consequences of Childhood Maltreatment and Adverse Childhood Experiences

Abstract: Childhood maltreatment (CM) and adverse childhood experiences (ACEs) are two primary forms of interpersonal victimization that have been associated with a host of deleterious health outcomes. Studies over the past decade have begun to use a range of biologically informed methods to better understand the role biology plays in the relationship between CM, ACEs, and later life outcomes. This line of research has shown that both forms of victimization occur at sensitive periods of development, which can increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 116 publications
(188 reference statements)
0
6
0
Order By: Relevance
“…These ndings, and the large body of evidence outlining the detrimental impact of childhood maltreatment on biological systems (e.g. HPA axis, in ammation etc) (20), highlight that the mechanisms linking childhood adversities to depression and obesity are not fully explained by socioeconomic status. Therefore, combining childhood adversities and low socioeconomic status as the antecedent exposure, allows for a more comprehensive understanding of how childhood stressors impact mental, physical, and comorbid health outcomes, and ultimately examines cumulative effects of stressors which may surpass the impact of socioeconomic status alone.…”
Section: Introductionmentioning
confidence: 99%
“…These ndings, and the large body of evidence outlining the detrimental impact of childhood maltreatment on biological systems (e.g. HPA axis, in ammation etc) (20), highlight that the mechanisms linking childhood adversities to depression and obesity are not fully explained by socioeconomic status. Therefore, combining childhood adversities and low socioeconomic status as the antecedent exposure, allows for a more comprehensive understanding of how childhood stressors impact mental, physical, and comorbid health outcomes, and ultimately examines cumulative effects of stressors which may surpass the impact of socioeconomic status alone.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively new approach is the use of genetic data as a surrogate for exposure, given that genetic markers are affected by types of biases (e.g., weak instrument, population stratification, pleiotropy) that are different from the sources of bias that commonly affect observational studies and produce non-causal results (e.g., residual confounding, reverse causation, information bias) [ 54 56 ]. To date, the use of genetic data as a proxy for childhood maltreatment has been limited [ 56 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has generally shown that ACEs are associated with higher risk levels for a variety of biological measures, although findings across studies are not always consistent. Two recent reviews of studies of negative childhood experiences and biomarkers of health, one summarizing findings from 40 studies between 2007 and 2017 [ 9 ] and the other summarizing findings from 199 studies conducted between 2010 and 2020 [ 10 ], report that some studies of childhood adversity and endocrine biomarkers, often cortisol or dehydroepiandrosterone (DHEAS), find a positive relationship while others find a negative relationship. One of the reviews notes that results sometimes depend on whether cortisol levels are based on saliva, urine, or blood [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the reviews notes that results sometimes depend on whether cortisol levels are based on saliva, urine, or blood [ 9 ]. Most of the reviewed studies find that childhood adversity is associated with elevated levels of individual biomarkers that reflect inflammation, such as interleukin 6 and C-reactive protein, but the results are not always significant and can differ depending on the measure of childhood adversity [ 9 , 10 ]. Similarly, findings are also mixed for biomarkers related to cardiovascular and metabolic function and measures of overall physiological dysregulation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%